Structural, microstructural and temperature dependent magnetic properties of Mg–Ni doped CoCr2O4 ceramics. Issue 8 (15th April 2022) - Manjunatha, K.; Si, Ping-Zhan; Jagadeesha Gowda, G.V.; El-Denglawey, A.; Jagadeesha Angadi, V.
Abstract: In the present work, [Co(1-(x + y)) Mgx Niy ][Cr2 ]O4 (CMNCr)(where, x = y = 0, 0.10, 0.20) NPs are examine in detail by using experimental results. Solution combustion method is adopted to prepare the CMNCr NPs. Experimental results were studied to understand structure (using XRD), microstructure (using SEM) and magnetic behaviour (using SQUID). The structural analysis was confirmed a single-phase spinel cubic structure with singular structural distortions associated with Mg–Ni doping and the generation of metal vacancies. SEM micrographs of all samples reveal their highly porous nature. EDS was utilized to examine the elemental analysis of the samples. The formation of spinel cubic structure without impurity were also confirmed by Fourier-transform infrared (FTIR) spectroscopy and the same tool is used to investigate the absorption bands related to the A-site and B-site. For all samples, paramagnetic phase to ferrimagnetic phase transition observed at TC and conical spiral spin order transition observed at TS . The curie temperature is found to be 98 K, 89 K, and 85 K for [Co][Cr2 ]O4, [Co0.8 Mg0.1 Ni0.1 ][Cr2 ]O4 and [Co0.6 Mg0.2 Ni0.2 ][Cr2 ]O4 samples, respectively. The spiral transition temperature is found to be 26 K, 14 K and 8 K for [Co][Cr2 ]O4, [Co0.8 Mg0.1 Ni0.1 ][Cr2 ]O4 and [Co0.6 Mg0.2 Ni0.2 ][Cr2 ]O4 samples, respectively. All of the samples exhibit paramagnetic behaviour above TC . The negative magnetization effect were observed in [Co0.6 Mg0.2 Ni0.2 ][Cr2 ]O4 NPs. 20% of Mg and 20% of Ni substitution to Co site in [Co][Cr2 ]O4 leads to the evident magnetization reversal at the compensation temperature with an applied magnetic field of 100 Oe. The M − H loop at 10 K exhibits large coercivity due to the spiral spin ordering. This phenomenon of negative magnetization in the material results in a stable state of magnetization in the material, which has significant applications in the field of magnetic storage devices.